Patterns of Violence Victimization and Perpetration Among Adolescents Using Latent Class Analysis - Sessarego, Stephanie N. (Journal of interpersonal violence, 2021)
Research has identified interpersonal violence (a broad term that includes stalking, harassment, sexual assault, and physical dating violence) as a major problem among adolescents. Research suggests that there are different patterns, or classes, of interpersonal violence victimization and perpetration, but little of this work has focused on adolescents. In the current study, we conducted latent class analysis using a sample of 2,921 adolescent girls and boys in high school from northern New England to assess varying patterns of interpersonal violence victimization and perpetration over the past 2 months, specifically stalking, harassment, sexual assault, and dating violence. Four classes of violence victimization and perpetration were identified: (a) No Victimization or Perpetration class (n = 1,898, 65.0%), (b) Low Victimization and Perpetration class (n = 343, 11.7%), (c) Harassment Victimization Only class (n = 560, 19.2%), and (d) High Victimization and Low Perpetration class (n = 120, 4.1%). Several differences in classes emerged as a function of demographic and behavioral health variables. For example, the High Victimization and Low Perpetration class had the highest proportion of girls and youth with sexual minority status. Furthermore, youth in the High Victimization and Low Perpetration class also had a significantly higher proportion of class members endorsing depressed mood and engagement in binge drinking than the youth in other classes. These findings demonstrate the heterogeneity in patterns of interpersonal violence, which future research should seek to better understand in terms of etiology, outcomes, and best practices for prevention and intervention.